2017
DOI: 10.1097/qai.0000000000001527
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Lopinavir Hair Concentrations Are the Strongest Predictor of Viremia in HIV-Infected Asian Children and Adolescents on Second-Line Antiretroviral Therapy

Abstract: Background Children/adolescents display suboptimal antiretroviral therapy (ART) adherence and outcomes versus adults. Hair ART concentrations are objective adherence measures that predict viremia in adults but longitudinal data on hair levels in pediatric populations is limited. We assessed the predictive utility of hair lopinavir levels on viremia among youth on second-line ART. Methods We examined predictors of viremia (HIV-1 RNA >400 and >1000 copies/ml) at least 24 weeks after switch to lopinavir-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
(22 reference statements)
3
16
0
Order By: Relevance
“… 25–27 Interestingly, our study revealed that hair concentrations of 3TC and EFV, but not AZT, are the strongest independent predictor of virologic suppression. Our findings of hair concentrations of 3TC and EFV added evidence to existing studies that reported that hair concentrations of antiretrovirals (eg, TFV, 33 EFV, 43 , 45 NVP, 30 LPV, 31 , 32 , 34 ATV 28 , 34 ) were the strongest independent predictor of virologic suppression. Regarding the nonsignificant finding of hair AZT concentrations, the small sample size and lower hair AZT concentrations could contribute to this finding.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“… 25–27 Interestingly, our study revealed that hair concentrations of 3TC and EFV, but not AZT, are the strongest independent predictor of virologic suppression. Our findings of hair concentrations of 3TC and EFV added evidence to existing studies that reported that hair concentrations of antiretrovirals (eg, TFV, 33 EFV, 43 , 45 NVP, 30 LPV, 31 , 32 , 34 ATV 28 , 34 ) were the strongest independent predictor of virologic suppression. Regarding the nonsignificant finding of hair AZT concentrations, the small sample size and lower hair AZT concentrations could contribute to this finding.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the simultaneous determination of hair concentrations of antiretrovirals in multiple classes is technically possible. [21][22][23][24] However, major of the previous studies only investigated the association of hair concentrations of a single antiretroviral 13,[25][26][27][28][29][30][31][32][33] or antiretrovirals in a single class 34 with virologic outcomes. Limited data are available on the association of hair concentrations of antiretrovirals in multiple classes with virologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this was the first successful attempt to determine 2-OH NVP and 3-OH NVP and evaluate long-term adherence based on the concentrations of metabolites in human hair. Previous studies were limited to the detection of NVP metabolites in other biological samples, such as human serum [28] and for the adherence evaluation based on drug prototypes in hair [22][23][24][25]. Additionally, we found that NVP's metabolites showed high consistency with NVP in evaluating long-term adherence.…”
Section: Discussionmentioning
confidence: 78%
“…Existing studies utilize the concentrations of the drugs' prototype in hair to evaluate long-term adherence [22][23][24][25]. However, the antiretroviral drugs are mostly metabolized in the circulating system once orally administered and only a fraction of them remain as the prototype structure.…”
Section: Introductionmentioning
confidence: 99%
“…The University of California San Francisco‐Hair Analytical Laboratory (UCSF‐HAL) has quantified a number of ARVs in hair (e.g., atazanavir, 19 lopinavir, 20 ritonavir, 20 efavirenz, 20 nevirapine, 21 darunavir, raltegravir, dolutegravir, TFV/FTC, 22–29 ) for research projects over the past 15 years. Hair concentrations of ARVs have been shown to be strong predictors of virologic response for a variety of ARVs, including TFV/FTC 30–41 …”
Section: Introductionmentioning
confidence: 99%